MMP-8 deficiency increases TLR/RAGE ligands S100A8 and S100A9 and exacerbates lung inflammation during endotoxemia. - Adrián González-López; Alina Aguirre; Inés López-Alonso; Laura Amado; Aurora Astudillo; María Soledad Fernández-García; María F Suárez; Estefanía Batalla-Solís; Enrique Colado; Guillermo M Albaiceta (PLoS ONE, 2012)
Matrix metalloproteinase-8, released mainly from neutrophils, is a critical regulator of the inflammatory response by its ability to cleave multiple mediators. Herein, we report the results of a model of endotoxemia after intraperitoneal LPS injection in mice lacking MMP-8 and their wildtype counterparts. Control, saline-treated animals showed no differences between genotypes. However, there was an increased lung inflammatory response, with a prominent neutrophilic infiltration in mutant animals after LPS treatment. Using a proteomic approach, we identify alarmins S100A8 and S100A9 as two of the main differences between genotypes. Mice lacking MMP-8 showed a significant increase in these two molecules in lung homogenates, but not in spleen and serum. Mice lacking MMP-8 also showed an increase in MIP-1α levels and a marked activation of the non-canonical NF-κB pathway, with no differences in CXC-chemokines such as MIP-2 or LIX. These results show that MMP-8 can modulate the levels of S100A8 and S100A9 and its absence promotes the lung inflammatory response during endotoxemia.